Vicia faba root development: a partial analysis with 5-aminouracil - Rudolph, John (My University, 1971)
Experiments described in this study were carried out 1n order to (a) extend previous studies on the analysis of the response to 5-aminoura.cil to small primordia and primary roots of Vicia faba and (b) to determine whether treatment with deoxynucleos1des would alter the cell's response to 5-aminouracil , either in DNA synthesis or at the S -G2 transition block.
The present study reveals that the population heterogeneity, which was found to exist in lateral roots, just emerged roots, very large primordia, and large primordia, is also present in primary roots and small primordia: also, that the ratio of fast cycling cells to slow cycling cells remains constant throughout root development.
All root meristems of V. faba exhibited the same general pattern of recovery after exposure to 5-aminouracil, i.e. the initial drop in mitotic index was followed by an increase to a value above controls. Variations between the different developmental stages were seen in (a) the time of onset of recovery, (b) the time of the appearance of the peak of mitoses, and (c) the degree of synchronization of recovery.
Data from post-5-aminouracil nucleoside treatments revealed that the nucleosides were unable to produce a reversal of the 5-aminouracil-induced block at the S -G2 transition, but were able to increase the rate of DNA synthesis and thus alter one of the effects of 5-aminouracil on cell cycle kinetics.
Keywords: Vicia faba; 5-aminouracil; small primordia; deoxynucleosides